Relasi Kuasa Dalam Film High & Low: The Worst X Cross Karya Norihisa Hiranuma dan Daisuke Ninomiya - Nur Hasliza Maulina; Sri Oemiati (Jurnal Ilmiah Global Education, 2026)
This study examines the representation of violence and power in the film High & Low: The Worst X Cross using Michel Foucault's theory of power relations with the aim of describing how the relationship between power and violence is interrelated in shaping identity and social dynamics in film. The method used is qualitative descriptive, with data collected through dialogue observation, scene analysis, and narrative and visual film studies. The analysis is focused on the concepts of power over the body, power over the mind, elements of power, and resistance. The validity of the data is maintained through conformity with the realistic context of the film. The results of the study show that this film shows the relationship of power over the body through the discipline and training of gang members, the relationship of power over the mind through psychological and ideological influences that form awareness and loyalty, elements of power that arise through symbols, rituals, and group structures, and resistance as a form of resistance to domination.